Synergistically enhanced photocatalytic reduction of CO2 on N–Fe codoped BiVO4 under visible light irradiation. Issue 32 (8th August 2017) - Li, F.; Zhang, L.; Chen, X.; Liu, Y. L.; Xu, S. G.; Cao, S. K.
Abstract : Synergistically enhanced visible-light-driven catalytic reduction of CO2 with H2 O to CH3 OH over N–Fe codoped BiVO4 . Abstract : A N and Fe codoped monoclinic BiVO4 (N–Fe-BVO) photocatalyst was prepared via a conventional sol–gel method and was evaluated for the photocatalytic reduction of CO2 with H2 O under visible-light irradiation (>400 nm). As revealed by the structural and photoelectric characterization, the doped N and Fe species can enter the lattice of BiVO4 and induce the codopant levels in the forbidden region of BiVO4, which helps in increasing visible-light absorption, suppressing charge recombination and promoting charge migration. Compared to pure or single-doped BiVO4, the N–Fe-BVO photocatalyst exhibited substantially improved visible-light photocatalytic activity for CO2 reduction, with the highest hydrocarbon generation rate of 27 μmol h −1 gcat −1 and the corresponding quantum efficiency of 1.86% being obtained. The enhanced photocatalytic activity of N–Fe-BVO can be attributed to the synergistic effect of the simultaneous presence of the Fe and N dopants, and the possible photocatalytic mechanism was also proposed based on the characterization results.